OWL1 Kunst in Ostwestfalen-Lippe : Albrecht Brusselmans Budde Fuchs Gensheimer Gröting Höger Katz Lison Masé Meinders Meyer Mühloff/Vossiek/Ek Müller Neumann Raab Rose Rosenbohm Schmidt Schuck Sonntag Stollhans Waesch Wedgwood-Ben Weizenfeld - Herford, Marta; Benedetti, Lorenzo; Fast, Friederike (Bielefeld : Keber, 2007)
Albrecht, Susanne ; Brusselmans, Ellen ; Budde, Anika ; Fuchs, Jan ; Gensheimer, Christine ; Gröting, Asta ; Höger, Angelika ; Katz, Kimo ; Lison, Thomas ; Masé, Elisabeth ; Meinders, Sandra ; Meyer, Gabriele Undine ; Mühlhoff, Martin ; Vossiek, Christian ; Müller, Matthias ; Neumann, Andreas ; Raab, Emanuel ; Rose, Anette ; Rosenbohm, Lars ; Schmidt, Erik ; Schuck, Nicole ; Sonntag, Alexandra ; Stollhans, Jürgen ; Waesch, Wolfgang ; Wedgwood-Benn, Kristine ; Weizenfeld.
OWL1 - Kunst in Ostwestfalen-Lippe, Marta Herford, Herford, 01. November 2007 - 13. Januar 2008
boek